Valproate in Conversion Disorder: A Case Report - Antonino Messina; Anna Maria Fogliani (Case Reports in Medicine)
Few data are in literature about the pharmacological treatment of conversion disorder and there are not any studies about the use of Valproate extended release (ER) in treating conversion disorder. In this article, we are reporting a case of an Italian woman with a diagnosis of conversion disorder treated effectively and quickly by Valproate ER.